The last brickmaker in America [videorecording (DVD)] - Champion, Gregg, 1956-; Poitier, Sidney; Newton, Cody; Laurie, Piper, 1932- (Phase 4 Films, 2011)
A man who has just lost his wife and whose brickmaking job is becoming obsolete finds a purpose when a troubled thirteen-year-old boy works for him over the summer.